Evaluation of Antioxidants, Antibacterial and Antidiabetic Activities of Aqua-alcoholic Marjoram Extract - Kadhim K. Ghudhaib; Fayhaa M. Khaleel (مجلة بغداد للعلوم, 2024)
Plant extracts possess special significance towards human health and vital activities for a wide range of diseases. The current study aims at verifying the presence of active ingredients in marjoram leaves extract, and determining antioxidants, antibacterial and antifungal activities, LD50 and its antidiabetic activity. The active ingredients were qualitatively analyzed by specific test methods. Antioxidant, LD50, antibacterial and antifungal activities were measured by their standard method. The antidiabetic activity was   determined by assessed hyperglycemia, hyperlipidemia   and liver functions by spectrophotometric methods.  The results confirmed the presence of several active components including flavonoids, alkaloids, terpenoids, tannins, and saponins. Also, the results of antioxidants activity showed that marjoram leaves extract possesses an antioxidant activity similar to ascorbic acid. LD50 results revealed that the allowed dose is 12.5 mg/ml. Biological activity results indicated that marjoram leaves extract possesses antibacterial and antifungal activities against wide range of pathogenic bacteria and fungi, but there is no effect of extract on E. coli and Staphylococcus aureus even at high concentrations. Marjoram extract revealed high antidiabetic activity when treated for two weeks 4mg of the extract daily. Also, lipid profile and liver functions, and testosterone levels were improved after treatment in the diabetic group related to the control group. It can be concluded that marjoram leaves extract has high antioxidant activity with high biological activity and high antidiabetic activity with a significant enhancement of fertility affected in diabetes and a high level of tolerated doses according to the LD50 value.